2021
DOI: 10.1093/fampra/cmab068
|View full text |Cite
|
Sign up to set email alerts
|

Facial paralysis and vaccinations: a vaccine adverse event reporting system review

Abstract: Background Vaccinations are a cornerstone of preventative medicine in the USA. However, growing concerns regarding facial nerve palsy following vaccination exist. Objective This study aims to assess the occurrence of facial palsy as reported by the Vaccine Adverse Event Reporting System (VAERS) database. Methods A retrospective analysis of the VAERS database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Although controversial in the scientific literature (22), our study provides evidence from China to support that influenza vaccination does not significantly increase the risk of PFP. The possibility of vaccine-induced immune-mediated adverse effects has raised concerns about a link between vaccines and peripheral facial paralysis (15). However, our data did not identify a significant association between vaccination and PFP, which is consistent with the findings of other studies also designed for SCCS (6)(7)(8)(9).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although controversial in the scientific literature (22), our study provides evidence from China to support that influenza vaccination does not significantly increase the risk of PFP. The possibility of vaccine-induced immune-mediated adverse effects has raised concerns about a link between vaccines and peripheral facial paralysis (15). However, our data did not identify a significant association between vaccination and PFP, which is consistent with the findings of other studies also designed for SCCS (6)(7)(8)(9).…”
Section: Discussionsupporting
confidence: 90%
“…The possibility of vaccine-induced immune-mediated adverse effects has raised concerns about a link between vaccines and peripheral facial paralysis ( 15 ). However, our data did not identify a significant association between vaccination and PFP, which is consistent with the findings of other studies also designed for SCCS ( 6 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not in case reports but in review articles, facial palsy is rare and its relationship with vaccination is not clear. 2 7 Similarly, VFP has also been reported and there are 2 studies about VFP associated with COVID-19 vaccination. 8 9 Lehrer et al 9 have reported 2 cases of unilateral VFP after BNT162b2 vaccination.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, it is worth mentioning that the influenza vaccine has been previously linked to an increased incidence of Bell’s palsy. The mechanism of this was also thought to be the reactivation of latent HSV-1 in the geniculate ganglion of the facial nerve, which in turn caused inflammation of the nerve [ 16 , 44 ]. Based on several hypotheses, the interaction between elements of the vaccine and specific human proteins’ immune cross-reactivity consequences in autoimmune disease, which may cause Bell’s palsy [ 45 ].…”
Section: Discussionmentioning
confidence: 99%